ANALYSIS OF ENGLISH MATRICULATION OBJECTIVE TEST AT DHYANA PURA UNIVERSITY IN THE YEAR OF 2019 - I Gede Neil Prajamukti Wardhana; I Putu Pranatha Sentosa; Ni Luh Desy Suari Dewi (STKIP Persada Khatulistiwa Sintang, 2021)
The study was conducted to analyze the quality of the 2019 English Matriculation objective test for which the quality was not known. This research is quantitative descriptive. This test was followed by 768 students. The research determined by a simple random sampling technique. The percentage of leeway for accuracy is 10% so that the number of samples specified is 90 respondents. The data collection technique in this research is documentation. The analysis technique in this study was carried out by testing the validity, reliability, level of difficulty, distinguishing power, and deceitful effectiveness so that it can be used to describe the quality of the English Matriculation test. The research results obtained in this matter were good, there were only 1 item (2%), 22 items needed to be repaired (44%), and 27 items (54%) were eliminated / removed. The preparation of the English Matriculation test was conducted through a focus group discussion. Evaluation of English matriculation questions should be carried out periodically in order to provide an overview of the quality of the questions. The items that have failed should not be used anymore, and the revised questions should be corrected by looking at the indicators of the cause of the failure. Increasing competency in writing questions can be done by participating in item analysis training or through tutorials on electronic media.Keywords: objective test; test analysis; test quality